The Influence of Soft Skills, Hard Skills and Work Motivation on Final Semester Students' Work Readiness at Dian Nuswantoro University - Aspandi, Muhamad Akbar Setiawan; Perdana, Tito Aditya; Hariyadi, Guruh Taufan; Sartika, Mila (Jurnal Economic Resource, 2025)
This study aims to evaluate the influence of soft skills, hard skills, and work motivation on the job readiness of final-year students at Universitas Dian Nuswantoro. The research employs a quantitative approach by distributing questionnaires as the data collection technique. The sampling method used in this study is purposive sampling, applying Cochran's formula, with a total sample of 100 respondents, consisting of final-year students at Universitas Dian Nuswantoro. The data analysis technique is conducted using IBM SPSS Statistics software. The results of the study confirm that all variables, soft skills, hard skills, and work motivation significantly influence the job readiness of final-year students at Universitas Dian Nuswantoro.